2018
DOI: 10.3892/etm.2018.5887
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte depletion does not affect the in�vitro healing ability of platelet rich plasma

Abstract: The clinical use of platelet-rich plasma (PRP) containing or deprived of leukocytes remains a subject of debate and a controversial issue. It is not yet clear whether leukocyte content has a positive or negative effect on tissue healing processes. Several studies, conducted mainly in the orthopedic field, support the use of leukocyte-poor (LP) PRP, whereas other studies have not identified any significant differences between the use of LP and leukocyte-rich PRP. In the present study, the role of leukocytes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…The proliferation of fibroblasts is concentration dependent, and both platelet‐derived factors and plasma act synergistically. Previous research also found positive effects of PRP on fibroblast proliferation . Superior induction of proliferation with human platelet lysate compared to FCS has previously been described for different cell types such as mesenchymal stromal cells .…”
Section: Discussionsupporting
confidence: 51%
“…The proliferation of fibroblasts is concentration dependent, and both platelet‐derived factors and plasma act synergistically. Previous research also found positive effects of PRP on fibroblast proliferation . Superior induction of proliferation with human platelet lysate compared to FCS has previously been described for different cell types such as mesenchymal stromal cells .…”
Section: Discussionsupporting
confidence: 51%
“…In vitro, it has been shown that there is not a significant difference between the effect of LR-PRP and LP-PRP on wound healing, suggesting that the major benefits of PRP stem from growth factors rather than leukocytes. 53 Raeissadat et al studied LR-PRP injections in patients with knee OA and found significant improvement in pain, stiffness, functional capacity, and quality of life 6 months post-injection. 54 However, when comparing LR-PRP and LP-RPR, Braun et al reported that LR-PRP led to significantly increased cell death and expression of multiple proinflammatory markers such as IL-1β, IL-6, interferon gamma, and tumor necrosis factorα (TNF-α).…”
Section: Different Preparationsmentioning
confidence: 99%
“…The following two studies investigated the effects of MMPs within their PRP experiments. The first study examined fibroblast proliferation, MMP expressions and GF release after the treatment of LR-or LP-PRP within the dose ranges of 0.3 -3 x 10 6 plt/μl [44]. The outcomes demonstrated fibroblast proliferation increased 2.5-fold for both samples compared to the untreated cells; however, no significant differences occurred between the PRP groups.…”
Section: Lr-prp Lp-prp Mmp Fibroblast Proliferation and Gfsmentioning
confidence: 99%